ANALISA LAPORAN KEUANGAN SEBAGAI DASAR PENILAIAN KINERJA PERUSAHAAN ( STUDI KASUS PADA PT NAC GLOBAL JAKARTA ) - Hartoko, Muhammad Setiadi (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2015)
Companies need to analyze the financial statements for the financial statements used to assess the performance of the company and is used to compare the condition of the company from the previous year to the current year if the company is increasing or not so that companies consider the decision to be taken for the coming year in accordance with the company's performance in order to know the condition of the financial statements NAC Global Jakarta in 2013 and 2014 as well as the performance of PT NAC Global Jakarta, based on analysis of liquidity ratios, solvency and profitability. In acquiring the data the authors used two methods of research that studies Field (Field Research) and Library Studies (Library Research) with the results of the financial statements of income PT NAC Global Jakarta in 2014 increased by 43.49% from 2013 to not be able to cover expenses incurred and 2014 PT Global Jakarta NAC profit decreased by 55.67% or profits obtained only Rp. 319 783 591. In addition the balance sheet, PT NAC Global Jakarta increased by 24.65% as well as total liabilities and capital of PT NAC Global Jakarta, which increased by 24.65%.